Existence, experience, and ethics : essays for S.A. Shaida - Shaida, S. A. (Sultan Ali).; Raghuramaraju, A. (New Delhi : D.K. Printworld, 2000)
Festschrift in honor of S.A. Shaida; contributed research papers.
Includes bibliographical references and index.
Keywords: EXISTENTIAL ETHICS; SELF; EXISTENTIALISM; PHILOSOPHY; ETHICS